Profitability of garlic (Allium sativum L.) cultivation in some selected areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2014)
The current production of garlic cant meet up the increasing demand of Bangladesh. Due to unknown reasons, the area and production of garlic have not been increased at desired level. Therefore, the study was conducted in Magura and Faridpur districts during 2008-2009 to analyze the relative profitability, input-output relationship, and constraints to garlic production. Primary data were collected from 100 randomly selected garlic farmers for the study. Per hectare costs of garlic cultivation were Tk. 65493 and Tk. 51747 on full cost and variable cost basis. The major share of total cost was human labour (30%) and seed (25%). The yield of garlic was 6.15 metric tons per hectare. The gross margin and net return were Tk. 70660 and Tk 56914 per hectare, respectively. The benefit cost ratio was 1.87. The net returns from garlic cultivation were 68%, 59%, and 0.64% higher than mustard, groundnut and cabbage cultivation. Cobb-Douglas production function revealed that human labour, land preparation cost, manure, TSP, irrigation and insecticide had positive effect on the yield of garlic. Non-availability of HYV garlic seed, lack of technical knowledge about improved cultivation practices of garlic, infestation of insects and diseases and low market price were the major problems for garlic cultivation. DOI: http://dx.doi.org/10.3329/bjar.v38i4.18944 Bangladesh J. Agril. Res. 38(4): 589-598, December 2013